Characteristics of stem respiration in black spruce (Picea mariana) stand, interior Alaska - Kim, Yongwon; Lee, Bang-Yong; Kim, Seong-Deog; Suzuki, Rikie (Polar Science, 2021)
Boreal forests account for roughly one third of the carbon sequestered in terrestrial ecosystems, and the high-latitude boreal ecosystem they make up has been consequently vulnerable to recent climate change. This study investigated stem respiration of Alaska dominant black spruce trees in interior Alaska during the growing season of 2007. The continuous measurement of stem respiration was conducted in black spruce trees of four different ages (4.3, 7.2, 9.8, and 13.5 cm in diameter at breast height (DBH)) in interior Alaska, using a CO2 analyzer, a 12-V pump, chambers, and a data-logger. Mean stem respiration is 0.014 ± 0.006 mg CO2 m−2 s−1 (range 0.003–0.039 mg CO2 m−2 s−1) in different aged four black spruce trees, indicating remarkably temporal variations in stem respiration with temperatures in air and stem. We found that metabolism is 1.5-fold higher in the younger black spruce tree than in the older. Temperatures in air and stem are significant regulators in regulating stem respiration. The stand-level annual stem respiration simulated by Q10 value based on air temperature is 73.9 g CO2 m−2, corresponding to 5.0% of the ecosystem respiration (Re) estimated by eddy covariance tower in 2007. Our findings demonstrate that stem respiration is a significant component in the scale-up of the regional carbon budget in a black spruce forest of interior Alaska. journal article